A Quantitative Analysis of Re-offense among Delinquent Foster Care Youth in Georgia - Jones, Brian Keith (2019)
Nationwide more than 2 million youth are placed in custody annually, approximately 80,000 children return home, and more than 70% have a diagnosable mental disorder. The purpose of this quantitative study was to examine the outcomes of 311 youth released from secure residential facilities in Georgia between January 2012 thru May 2017. In the dataset, 136 youth returned to regular homes, 128 returned to group homes (GC), and 47 returned to traditional foster homes (TFC). The goal of the study was to examine the differences in probation outcomes based on the type of placement. For the purpose of the study, probation success was defined as having no additional placements in a secure residential facility within 365 days of release. To provide additional context, mental health status, race, sex, and age were analyzed. Binomial logistic regression and chi-square tests were performed to answer the research question. The tests did not reflect a statistically significant difference in the outcomes. However, the analysis did reflect that race and placement type had some effect on probation success. For race, success was 15.4% for black, 24.0% for white, and 24.1% for other. For placement type, probation success was 15.6% for youth returning to GC, 20.6% for youth returning to regular homes, and 23.4% for youth returning to TFC. As reflected in the literature, issues such as lack of proven programs in the community, mental health, and family impact the outcomes of delinquent youth in foster care. This study and the literature reflect the need for social change which can occur when the needs of delinquent juveniles supervised in foster care are addressed systematically